The Islamic Religious Education Students’ Attitudes Toward English Learning: A Case Study at State Islamic University - Dewi Warna; Aldika Gardana; Nur Latiffah; Alviola Gardana (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
Becoming proficient in English requires more than just knowledge of vocabulary and grammar rules; it also requires a positive attitude toward language learning. This study aims to investigate the students’ attitudes toward English learning. A quantitative approach was employed in this study, utilizing a data collection technique through a questionnaire survey. The data was analyzed using descriptive statistical analysis. The respondents of this study consisted of 75 students from three classes in the first semester of Islamic Education at State Islamic University Raden Fatah, who were taking the English Subject. In collecting the data, this study used Orwig's Language Learning Attitudes Questionnaire. The findings show that out of 75 students, 17 students (22.66%) slightly hold self-image; Twenty-nine students (38.66%) neither hold nor lack inhibition; Twenty-five students (33.33%) slightly lack risk-taking; Thirty-nine students (52%) neither hold nor lack ego permeability; Forty-two students (56%) slightly hold motivation; Forty-six students (61.33%) neither hold nor lack ambiguity. This study's findings demonstrate the vast diversity of psychological profiles that exist among students, encompassing attitudes toward inhibition, self-image, risk-taking, ego permeability, motivation, and tolerance of ambiguity. While the variances in slight to moderate endorsements or lack thereof reflect individual disparities in the students' psychological orientations, the prevalence of neutral attitudes suggests a degree of ambivalence or equilibrium in these psychological categories.